Effect of frequent exposures of various indigenous sugars on cariogenicity of a biofilm caries model - Karunanidhi Kannappan; Preetha Elizabeth Chaly; Shyam Sivasamy (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to assess and compare the cariogenicity of indigenous sugars (palm sugar, jaggery, and brown sugar) and refined sugar at different frequencies of exposure through a biofilm caries model. Methodology: This in vitro study was conducted on 60 extracted human premolar teeth which were randomly divided into four groups (refined sugar, jaggery, palm sugar, and brown sugar) with each group being exposed to their respective sugars at one, three, and five frequencies for 5 min at defined time periods with five sample teeth for each exposure (4 × 3 × 5 = 60). The acidogenicity of biofilm was found by a 5-day pH cycling model. After 5 days, enamel demineralization, protein content, and polysaccharide formation of the biofilm following exposure to various sugars at various frequencies were assessed and compared. Statistical analyses were done using a one-way analysis of variance for intergroup comparisons between various sugars at various levels of frequencies. Results: The enamel demineralization was found to be least in palm sugar with mean percentage surface hardness loss of 8%, 17%, and 25% at one, three, and five frequencies of exposures and this was found to be statistically significant compared to other sugars (P < 0.001). The acidogenicity of biofilm increased with an increase in the frequency of exposures, but none of the indigenous sugars had a drop below 5.5 (critical pH) at a single frequency of exposure indicating less acid production at minimal exposure. The protein content of the biofilm exposed to palm sugar was less on comparison with other sugars and it was found to be statistically significant (P < 0.001). The polysaccharide formation of all sugars was similar at each frequency of exposure and was statistically nonsignificant. Conclusion: From the results obtained, it was concluded that though cariogenicity increased in all sugars with an increase in frequency of exposure, the level of cariogenicity was least in palm sugar compared to other sugars used in the study. Hence, it is recommended to use palm sugar as an alternative to refined sugar.